2015
DOI: 10.1039/c5ra00791g
|View full text |Cite|
|
Sign up to set email alerts
|

Sustainable construction: admicellar catalysed synthesis of pyrimido[4,5-b]quinolines in an aqueous system

Abstract: A simple and highly efficient strategy has been documented for the rapid and convenient synthesis of pyrimido[4,5-b]quinoline from aldehydes, 2-hydroxynaphthalene1,4dione and 6-aminouracil in the presence of nano ZnO under aqueous admicellar system at 80 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In the other report, Siddiqui and co-workers 75 Choudhury and co-workers demonstrated a facile and green pathway to prepare several condensed 1,4dihydropyridines fused with 2-hydroxynaphthalene-1,4-dione (33) under microwave heating conditions via Knoevenagel-Michael addition (Scheme 22). 76 They have reported the three-component reaction of 2hydroxynaphthalene-1,4-dione (33), aldehydes (1), and 6-aminouracil derivatives (2) in acetic acid/water (1:1;v/v) under microwave irradiation.…”
Section: Synthesis Of Pyrimido-pyrimidine Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the other report, Siddiqui and co-workers 75 Choudhury and co-workers demonstrated a facile and green pathway to prepare several condensed 1,4dihydropyridines fused with 2-hydroxynaphthalene-1,4-dione (33) under microwave heating conditions via Knoevenagel-Michael addition (Scheme 22). 76 They have reported the three-component reaction of 2hydroxynaphthalene-1,4-dione (33), aldehydes (1), and 6-aminouracil derivatives (2) in acetic acid/water (1:1;v/v) under microwave irradiation.…”
Section: Synthesis Of Pyrimido-pyrimidine Compoundsmentioning
confidence: 99%
“…Scheme 21. Synthesis of 1-methyl-5-phenylbenzo[g]pyrimido[4,5-b]-quinoline-2,4,6,11(1H,3H)-tetraone 75. …”
mentioning
confidence: 99%
“…Siddiqui et al 362 reported the synthesis of nano ZnO 361 using zinc acetate dehydrate and potassium hydroxide and characterized its nano nature (15-25 nm) via EDS, TEM and XRD. Further, they also used the nano ZnO for the synthesis of pyrimido [4,5-b]quinolines (172e, Scheme 200) using benzaldehydes (21a), 2-hydroxynaphthalene-1,4-dione (191) and 6-aminouracil (182b) in a green admicellar aqueous solution of CTAB as an emulsifying agent.…”
Section: Znnp-catalyzed Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Nano zinc oxide‐catalysed pyrimido[4,5‐ b ]quinoline synthesis via an admicellar approach was designed by Siddiqui et al . Cetyl trimethyl ammonium bromide (CTAB)‐water mediated reaction of 2‐hydroxynaphthalene‐1,4‐dione, 6‐aminouracil and aldehydes proceeded using 15 mol % ZnO NPs at 80 °C (Scheme ).…”
Section: Heterocyclic Compoundsmentioning
confidence: 99%